A note on genetic isolation of Mediterranean sperm whales (Physeter macrocephalus) suggested by mitochondrial DNA - Drouot, Violaine; Berube, Martine; Gannier , Alexandre; Goold , John C.; Reid , Robert J.; Palsboll , Per J. (J. Cetacean Res. Manage., 2023)
Thirteen sperm whales were sampled, using sloughed skin, in the Mediterranean Sea during six distinct encounters. Individuals were discriminated using the results of molecular sexing, mitochondrial control region sequencing and microsatellite genotyping (3 loci). Samples from 57 specimens were available from sperm whale strandings on northern European coasts. The first ~ 200bp of the mitochondrial DNA (mtDNA) control region of each sample were sequenced and three different haplotypes were identified. The frequency of each haplotype was significantly different between the Mediterranean Sea and the eastern North Atlantic, suggesting that sperm whales in the two areas comprise different maternal entities.